Perancangan Maskot LLDIKTI 4 sebagai Strategi Peningkatan Nilai-Nilai dan Citra Positif Kelembagaan - Fahran Ferial Agustian; Rosa Karnita (Jurnal Riset Multidisiplin Edukasi, 2025)
LLDIKTI 4, a part of the Ministry of Education, Culture, Research, and Technology, plays an important role in managing higher education in West Java and Banten. However, the institution faces challenges in increasing brand awareness due to a lack of engaging visual identity. This research developed a mascot incorporating elements of West Javanese culture and LLDIKTI 4's identity, designed in a cartoon style targeting audiences aged 18–45. The mascot has proven effective in creating emotional connections, conveying institutional values, and boosting engagement across various media platforms. As a result, the mascot helps build LLDIKTI 4's professional image, reaches a broader audience, and increases public trust through social media, brochures, and the website. The mascot is also expected to attract the interest of younger generations.